Construct an instructional approach based on collaborative learning and reflective learning for enhance students’ analytical thinking and critical thinking skills - Guo, Rui; Jantharajit, Nirat; Thongpanit, Phichittra (Asian Journal of Contemporary Education, 2024)
In the context of rapid globalization and digitalization, the development of students' critical and analytical thinking skills is increasingly prioritized in education. This study aims to address the gap in instructional models by designing an eight-step instructional model that integrates collaborative and reflective learning strategies to enhance these essential skills. Drawing on social constructivist theories and Dewey's reflective thinking framework, the research develops a comprehensive model that includes phases such as goal setting, team formation, exploration, collaborative practice, reflection, integration, and feedback. The findings suggest that this model significantly improves students' analytical and critical thinking abilities by promoting structured collaboration and intentional reflection. Through diverse group interactions and continuous self-assessment, students achieve a deeper understanding and critical analysis. The model's iterative feedback mechanisms also contribute to sustained improvements in student learning outcomes. This study introduces an original instructional model that theoretically supports the enhancement of analytical and critical thinking skills through a systematic integration of collaborative and reflective learning, offering practical implications for educators seeking to foster these higher-order thinking skills in students.